(untitled) (Research, Society and Development, 2024)
A Lean Six Sigma diagnosis was conducted to identify the weaknesses in the patient referral flow from femur fracture to the surgical center within 72 hours. This is a retrospective study involving patients who underwent femur fracture surgery between July 2023 and June 2024. Patients were divided into 2 groups: before team communication from July to December 2023 and after adjustment, from January to June 2024. The measured times refer to the patient’s entry into the hospital until they were referred to the services: T1: registration and triage, T2: clinical care and request for diagnostic and laboratory tests, T3: cardiac risk, T4: test results and surgical scheduling; T5: entry into the surgical center. 51 patients were included in the first group and 39 in the second group and it was observed that there was a reduction in the total time, after communication with the team, from 110.9h to 95.22h. There was a reduction in all times, except in the surgical risk assessment, where there was an increase in time from 18.04h to 25.88h. It was diagnosed the need to create different protocols for polytrauma patients or those using anticoagulant medication, as they generated outliers in the study, increasing the dispersion of times and preventing significant differences from being observed. The presence of cardiologists, number of hip surgery specialists and increase in days for echocardiogram, were pointed out as urgent corrections to the process to achieve the goal of 72 hours.